THE INFLUENCE OF PROMOTION THROUGH SOCIAL MEDIA , E-WOM AND BRAND AMBASSADOR ON EMINA PRODUCT PURCHASE DECISION (Case Study on Malikussaleh University Students) - Putri Aklima; Jullimursyida; Naufal Bachri; Mariyudi (International Journal of Social Science, Educational, Economics, Agriculture Research and Technology (IJSET), 2024)
This study aims to determine the effect of promotional strategies through social media, word of mouth, and brand ambassadors on purchase decisions for Emina products, with a case study focused on students at Malikussaleh University. This quantitative study uses multiple linear regression for model selection. The study uses primary and secondary data collected online via Google Forms distributed to Malikussaleh University student respondents. The sampling technique is non-probability sampling, where not all members have the same chance of being selected. The sample was selected based on particular criteria, aged 18 to 24 years and consumers of Emina products. A total of 100 respondents were sampled using the Slovin formula. Data analysis was performed using SPSS version 25. The results indicate that promotional strategies on social media have a positive and significant influence on purchasing decisions for Emina products among Malikussaleh University students. However, the word-of-mouth variable does not have a significant effect on purchase decisions. Brand ambassadors also have a positive and significant influence on purchase decisions for Emina products among Malikussaleh University students.